Associations between Socio-Demographic Factors and Hypertension Management during the COVID-19 Pandemic: Preliminary Findings from Malaysia - Elnaem, Mohamed Hassan Abdelaziz; Kamarudin, Nur Hasyimah; Syed, Nabeel Kashan; Huri, Hasniza Zaman; Dehele, Inderpal; Cheema, Ejaz (2021)
Abstract: The perspectives of hypertensive patients on the state of hypertension control during the ongoing pandemic restrictions have not been extensively studied in Malaysia. Therefore, this study aimed to assess the impact of socio-demographic factors, health literacy, and adherence on the overall hypertension management in a group of Malaysian hypertensive patients during the COVID-19 pandemic. An anonymous, online cross-sectional study was conducted over three months that involved a group of Malaysian adults with hypertension. A validated, self-administered 30-item questionnaire was prepared in Malay and English languages on Google Forms. The link was then distributed to participants on social media (Facebook and WhatsApp). Following survey validation, a pilot study with 30 participants who met the inclusion criteria was carried out. The total scores for health literacy, adherence, and pandemic impact on hypertension control were calculated and compared across all independent variables. In a total of 144 study participants, controlled blood pressure was reported in 77% (N = 111). There were good levels of adherence and health literacy scores but moderate levels of pandemic impact scores. The total adherence scores showed a statistically significant difference between age groups (2 = 6.48, p = 0.039) and those who reported having controlled and uncontrolled blood pressure (U = 1116, p = 0.001). Moreover, the analysis revealed statistically significant differences in total pandemic impact scores based on the age group (2 = 15.008, p = 0.001), household income (2 = 6.887, p = 0.032), employment (U = 1712, p = 0.006), and marital status (U = 520.5, p < 0.001). The youngest age group (18–39) years, the lowest income group, unemployed and unmarried individuals, had significantly higher pandemic impact scores. This denotes that those individuals were more prone to be negatively affected by the pandemic regarding their hypertension management. Most participants reported relatively controlled blood pressure and good levels of health literacy as well as adherence amidst the pandemic. To a moderate extent, study participants perceived that the pandemic had a negative effect on hypertension management. The perceived negative impact of the pandemic was attributed to several socio-demographic factors, such as age, household income, employment, and marital status.